76 - THE RECEPTION AT THE CLINIC OF A UNIVERSITY HOSPITAL, IN THE VIEW OF USERS (Fiep Bulletin - online, 2011)
This quantitative / qualitative study aims to analyze the ambulatory care at the Hospital Universitário Onofre Lopes (HUOL) and, as a guide, the host to the User. For this purpose were invited and interviewed 20 users. In the interviews, conducted in a space of 45 days, in this same time frame was used for daily field notes of observations more meaningful. In the analysis, we draw the sociodemographic profile of the group and identify their main complaints, problems and suggestions. For this, we construct graphs, tables and figures, and their statements stand out as a resource for better understanding of the subjective. The theoretical framework consisted of documents from the Ministry of Health about the admission and humanization, as well as studies of Merhy, Franco, Pinheiro, Matumoto, Mariotti, Teixeira, among others. The results point the ambulatory clinic of HUOL as a privileged and credibility, where users are, often, answers to their problems. However, these same users were unanimous in stating the difficulties they face in obtaining appoitments from the basic unit, to reach the hospital. Referring to the call, but feel satisfied with the care received, lists a number of problems, structural and relationship: lack of visual signaling information, wheelchairs, hygiene, waiting rooms that offer some comfort, and the inattention of some professionals. In summary, the study undertaken now, it allows us to state that there is actually studied, the host, in its fullest sense, however, the HUOL as teaching hospital, has all the potential to do it.
Keywords: Humanization; Reception; Ambulatory care